Effects of Azadirachta indica (Neem) seed extract on larvae and adult Anopheles mosquitoes in Nasarawa Local Government Area, Nasarawa State Nigeria. - Sunday Haruna; Patience Lama; Olayinka Michael; Adamu Ezekiel; Tongjura JDC; Ombugadu R.J (International Journal of Applied Biology, 2022)
Abstract Over the years, the use of agrochemicals has been one of the reasons for resistance of mosquitoes to insecticides, a negative trend that has been on the increase. This study was carried out to determine the effect of Azadirachta indica (neem) seed extract on the larvae and adult Anopheles mosquitoes in Nasarawa Local Government Area of Nasarawa state as a possible alternative to already existing insecticide against the parasite. The research was carried out at the insectary laboratory of Nasarawa state university Keffi. Impregnated papers of neem seed oil were used for adult Anopheles mosquitoes and the larviciding effect was also determined. Adult Anopheles mosquitoes exposed to impregnated papers of neem seed extract at different concentrations of 20%, 40%, 80% and 100% showed 5%, 29%, 66% and 91% respectively. Mortality rate was recorded at 24h of exposure with LC50 (Lethal concentration) of 4.45ml. The larvae were also exposed to different concentration of neem seed extract of 1%, 4%, 8% and 10% for 72h and the mortality rate was 100% with LC50 value (Lethal concentration) of 4.16ml. This implied that adult Anopheles mosquitoes will required more of the extract to achieve 100% mortality than larvae. Using Azadirachta indica (neem) seed extract as an anti-mosquito agent was more effective on the larvae of Anopheles mosquitoes than the adult Anopheles mosquitoes.